Perceived Value Mediation on Price and Product Quality Toward Purchase Intention of Balinese Masks - Kepakisan, I Nyoman Bagus Yoga; Putra, Ida Bagus Udayana; Amerta, I Made Suniastha; Setini, Made (International Journal of Management and Business Applied, 2026)
Purpose–This study aims to examine the effect of price and product quality on the purchase intention of Balinese masks in Mas Village, Gianyar, and to analyze the mediating role of perceived value in explaining the relationship between these variables within the context of cultural-based creative products. Methodology/approach–This research employs a quantitative explanatory approach using a survey method. Data were collected from 130 respondents who had experience purchasing or considering the purchase of Balinese masks. The sampling technique used purposive sampling. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test both direct and indirect (mediating) relationships among variables. Findings –The results indicate that price and product quality have a positive and significant effect on purchase intention. Both variables also significantly influence perceived value, which in turn positively affects purchase intention. Furthermore, perceived value is proven to significantly mediate the relationship between price and purchase intention, as well as between product quality and purchase intention. These findings confirm that consumer buying interest in cultural products is shaped not only by economic and functional evaluations but also by psychological value perception. Novelty/value –This study contributes to the literature by extending the application of the Theory of Planned Behavior and Perceived Value Theory in the context of traditional cultural handicraft products. Unlike prior studies that primarily focus on manufactured or standardized goods, this research emphasizes the mediating role of perceived value in cultural-based creative industries, particularly in Balinese mask products. The findings provide strategic insights for artisans and cultural entrepreneurs in strengthening pricing strategies, maintaining product authenticity, and enhancing perceived value to increase purchase intention.